Sonaravne usmeritve prihodnjega prostorskega razvoja Ljubljane - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Environmental protection in the Ljubljana city municipality is one of three basic (beside economic and social), but unequally treated spheres of sustainable urban development. Compared to other European cities of similar size, Ljubljana is not supposed to be among the most degraded urban areas. However, with some additions, the Spatial plan of the Ljubljana city municipality is a suitable expert scheme for more environmentally adjusted spatial development. Essential sustainable spatial challenges of cities policies in Ljubljana and Ljubljana city municipality are to protect the underground water of Ljubljansko polje, to calm down the suburbanization processes and road transport within the environmental limits.
Keywords: Ljubljana; urbani razvoj; prostorski razvoj; sonaravni razvoj; varstvo okolja; environmental protection; ecology; ekologija